Tianhuang formula reduces the oxidative stress response of NAFLD by regulating the gut microbiome in mice - Luo, Duosheng; Yang, Ling; Pang, Huiting; Zhao, Yating; Li, Kunping; Rong, Xianglu; Guo, Jiao (Frontiers in Microbiology, 2022)
Background The gut microbiome affects the occurrence and development of NAFLD, but its mechanism has not yet been fully elucidated. Chinese medicine is a new treatment strategy to improve NAFLD by regulating the gut microbiome. Tianhuang formula (TH) has been proved to have a lipid-lowering effect in which constituents of ginsenoside Rb1, ginsenoside Rg1, ginsenoside Rb, ginsenoside Re, and ginsenoside R1 from Panax notoginseng and berberine, palmatine, and coptisine from Coptis chinensis have low drug permeability, which results in poor intestinal absorption into the human body, and are thus able to come into contact with the gut microflora for a longer time. Therefore, it might be able to influence the gut microbial ecosystem, but it still needs to be investigated. Method The characteristics of the gut microbiome were represented by 16S rRNA sequencing, and the metabolites in intestinal contents and liver were discovered by non-targeted metabolomics. Correlation analysis and fermentation experiments revealed the relationship between the gut microbiome and metabolites. Blood biochemical indicators, liver function indicators, and oxidation-related indicators were assayed. H&E staining and Oil Red O staining were used to analyze the characteristics of hepatic steatosis. RT-qPCR and western blotting were used to detect the expression of genes and proteins in liver tissues, and fecal microbial transplantation (FMT) was performed to verify the role of the gut microbiome. Results Gut microbiome especially Lactobacillus reduced, metabolites such as 5-Methoxyindoleacetate (5-MIAA) significantly reduced in the liver and intestinal contents, the level of hepatic GSH and SOD reduced, MDA increased, and the protein expression of Nrf2 also reduced in NAFLD mice induced by high-fat diet (HFD). The normal diet mice transplanted with NAFLD mice feces showed oxidative liver injury, indicating that the NAFLD was closely related to the gut microbiome. TH and TH-treated mice feces both can reshape the gut microbiome, increase the abundance of Lactobacillus and the content of 5-MIAA in intestinal contents and liver, and improve oxidative liver injury. This indicated that the effect of TH improving NAFLD was related to the gut microbiome, especially Lactobacillus. 5-MIAA, produced by Lactobacillus, was proved with fermentation experiments in vitro. Further experiments proved that 5-MIAA activated the Nrf2 pathway to improve oxidative stress in NAFLD mice induced by HFD. TH reshaped the gut microbiome, increased the abundance of Lactobacillus and its metabolite 5-MIAA to alleviate oxidative stress, and improved NAFLD. Conclusion The study has demonstrated a mechanism by which the gut microbiome modulated oxidative stress in NAFLD mice induced by HFD. The traditional Chinese medicine TH improved NAFLD by regulating the gut microbiome, and its mechanism was related to the “Lactobacillus-5-MIAA-Nrf2” pathway. It provided a promising way for the intervention of NAFLD.